2009
DOI: 10.1161/atvbaha.108.181727
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 Receptor Expression Masks the Antiinflammatory and Glucose Uptake Capacity of Insulin in Vascular Smooth Muscle Cells

Abstract: Objective Insulin resistance of vascular smooth muscle cells (VSMCs) has been linked to accelerated atherosclerosis in diabetes; however, the effects of insulin on VSMCs remain controversial. Most VSMC insulin receptors are sequestered into insulin-insensitive hybrids with insulin-like growth factor-1 receptors (IGF1R). Thus we hypothesized that regulation of IGF1R expression may impact cellular insulin sensitivity. Methods and Results IGF1R expression was increased in aortas from diabetic mice. IGF1R overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…In accordance with our proposed mechanism for insulin resistance in human VSMCs (Fig. 8), disruption of IGF1R in breast cancer cells, osteoblast, and rat VSMC is followed by an increased fraction of insulin holoreceptors and reduced insulin resistance (Fulzele et al 2007, Zhang et al 2007, Engberding et al 2009). …”
supporting
confidence: 87%
“…In accordance with our proposed mechanism for insulin resistance in human VSMCs (Fig. 8), disruption of IGF1R in breast cancer cells, osteoblast, and rat VSMC is followed by an increased fraction of insulin holoreceptors and reduced insulin resistance (Fulzele et al 2007, Zhang et al 2007, Engberding et al 2009). …”
supporting
confidence: 87%
“…37 Recently, Cascella et al 38 reported that aldosterone accelerates the development of atherosclerosis via IGF1-mediated signaling in VSMCs. In addition, Engberding et al 9 reported that aortas of diabetic mice expressed significantly more IGF1R in all wall layers than did those of age-matched controls. However, it is methodologically difficult to distinguish the effects of IGF1R and IR, because both receptors partly share a common downstream signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Protein samples from VSMCs or aorta (600 g of protein) were immunoprecipitated by overnight incubation with anti-IR␤-subunit antibody, followed by immunoblot analysis with an antibody against IGF1R␤-subunit. 8,9 Real-Time Reverse Transcription-Polymerase Chain Reaction…”
Section: Western Blot Analysis and Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid receptors have been reported to function as IGF-IR thus having a high affinity for IGF-I but not for insulin (Soos et al, 1993). The fact that the IR β-subunit immunoprecipitated with antibodies against the IGF-IR was not activated by insulin ( Figure 1) and that the IR was activated by IGF-I 10 -8 M in preadipocytes but not in adipocytes is probably explained by insulin/IGF-I hybrid receptors (Frattali,Pessin, 1993;Engberding et al, 2009). …”
Section: Discussionmentioning
confidence: 98%